Flexible Electronics Based on Organic Semiconductors: from Patterned Assembly to Integrated Applications. Issue 11 (15th January 2023) - Liu, Haoran; Liu, Dong; Yang, Junchuan; Gao, Hanfei; Wu, Yuchen
Abstract: Organic flexible electronic devices are at the forefront of the electronics as they possess the potential to bring about a major lifestyle revolution owing to outstanding properties of organic semiconductors, including solution processability, lightweight and flexibility. For the integration of organic flexible electronics, the precise patterning and ordered assembly of organic semiconductors have attracted wide attention and gained rapid developments, which not only reduces the charge crosstalk between adjacent devices, but also enhances device uniformity and reproducibility. This review focuses on recent advances in the design, patterned assembly of organic semiconductors, and flexible electronic devices, especially for flexible organic field‐effect transistors (FOFETs) and their multifunctional applications. First, typical organic semiconductor materials and material design methods are introduced. Based on these organic materials with not only superior mechanical properties but also high carrier mobility, patterned assembly strategies on flexible substrates, including one‐step and two‐step approaches are discussed. Advanced applications of flexible electronic devices based on organic semiconductor patterns are then highlighted. Finally, future challenges and possible directions in the field to motivate the development of the next generation of flexible electronics are proposed. Abstract : Organic semiconductors are considered powerful materials in flexible functional applications due to their solution processability, being low cost, being lightweight, and natural flexibility. This review summarizes the key points of various patterning technologies of organic semiconductors on flexible substrates, as well as the sensitive and intelligent applications of flexible electronic devices based on them.